Low-sodium versus standard-sodium peritoneal dialysis solution in hypertensive patients: a randomized controlled trial - Rutkowski, Bolesław; Tam, Paul; van der Sande, Frank M.; Vychytil, Andreas; Schwenger, Vedat; Himmele, Rainer; Gauly, Adelheid (American journal of kidney diseases, 2016)
Peritoneal dialysis (PD) solutions with reduced sodium content may have advantages for hypertensive patients; however, they have lower osmolarity and solvent drag, so the achieved Kt/Vurea may be lower. Furthermore, the increased transperitoneal membrane sodium gradient can influence sodium balance with consequences for blood pressure (BP) control.
The Low Sodium Balance Study Group: V. Schwenger, A. Vychytil, G. Kopriva, F.M. van der Sande, C.J.A.M. Konings, P.L. Rensma, M. van Buren, L.J. Vleming, A. Książek, M. Klinger, B. Rutkowski, M. Myśliwiec, M. Nowicki, W. Sułowicz, W. Grzeszczak, P. Tam, D. Ouimet
Originally published online September 18, 2015
Gesehen am 07.05.2020